PREVALENSI PENYAKIT MATA PTERIGIUM PADA NELAYAN DI DESA BOGAK KABUPATEN BATUBARA PADA BULAN NOVEMBER - DESEMBER TAHUN 2020 - ANIZWA ZAIRINA RAHMA; HEPPY JELITA SARI BATUBARA (LP2MTBM MAKARIOZ, 2021)
Pterygium is a non-malignant fibrovascular growth, which is triangular in shape with a central apex or in the cornea.The results of the Basic Health Research (RISKESDAS) in 2013, the prevalence of pterygium in Indonesia was 8.3% withjobs as farmers/fishermen which had the highest prevalence of pterygium (15.8%). This research is a descriptive study withaapproach cross sectional and a sampling method with a purposive sampling method. The number of respondents whomatch the inclusion and exclusion criteria in this study amounted to 32 people. The measuring instrument in this study isconducting direct interviews as primary data. Distribution and frequency based on length of time as fishermen 5-10 years(3%), 10-20 years (16%),>20 years (81%), length of fishing 5-8 hours (12%),>8 hours (88% ), history of smoking (90.6%),family history (59.4%), grade II pterygium (56.3%). Hoped that the distribution and frequency of this pterygium can helpprevent the occurrence of pterygium and blindness due to advanced degrees of pterygium.